2022
DOI: 10.1155/2022/6941748
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Value on Combined Detection of Serum CA724, DKK1, and TK1 in Diagnosis of Gastric Cancer

Abstract: Objective. To explore the clinical value on combined detection of serum carbohydrate antigen 724 (CA724), secreted protein dickkopf-1 (DKK1), and thymidine kinase 1 (TK1) in the diagnosis of gastric cancer (GC). Methods. The clinical data of 63 GC patients (GC group) and 54 patients with benign gastric lesions (control group) admitted to Zhu Xianyi Memorial Hospital of Tianjin Medical University from June 2020 to June 2021 were retrospectively analyzed. The levels of serum CA724, DKK1, and TK1 in the two group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…TK1 , which is associated with CD8 + T cells [ 56 ], is a marker of abnormal tumor cell proliferation. Its concentration increases with lesion growth, disease progression, and distant metastasis [ 57 ]. In summary, our findings indicate a connection between GGT5 and memory CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…TK1 , which is associated with CD8 + T cells [ 56 ], is a marker of abnormal tumor cell proliferation. Its concentration increases with lesion growth, disease progression, and distant metastasis [ 57 ]. In summary, our findings indicate a connection between GGT5 and memory CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been pointed out that the incidence of GC is significantly correlated with gender, age, CEA, alpha-fetoprotein (AFP), CA125, CA199 and CA242 positive levels, and AFP, CEA, CA125, CA199 and CA242 positive levels are significantly higher in M1 GC patients than in M0 patients[ 27 ]. Wang et al [ 28 ] compared the serum CA724 levels between patients with benign gastric lesions and patients with GC, and the results showed that the expression of CA724 in the serum of patients with GC was significantly increased, and the area under the curve of serum CA724 in the diagnosis of GC was 0.849, with high sensitivity and specificity in differentiating GC, which is an important indicator for early screening and auxiliary diagnosis of GC. The above studies suggest that tumor markers such as CEA, CA199, and CA724 have the potential to be used as targets for the diagnosis and treatment of GC, and based on this, this study investigated the expression of serum CEA, CA199, and CA724 in GC with their correlation with clinicopathological features in order to prevent and control the incidence of GC early and improve the survival rate and quality of life of patients with GC.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors give an advantage to TK1 , since its tight association with the S phase, while Ki-67 is present in all phases of the cell cycle [ 63 , 65 ]. So far, TK1 has been applied as a biomarker in the lung [ 66 ], breast [ 64 ], prostate [ 63 ], and gastric cancer [ 67 ], and its overexpression was associated with poor prognosis. Furthermore, several studies identified TK1 ’s correlation with tumor aggressiveness [ 68 , 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%